Coastal flow simulation using SPH: Wave overtopping on an impermeable coastal structure - Didier, E. (2009)
Wave overtopping is a violent natural event that involves highly complex phenomenon such as large deformation of free surface, turbulence and eddy vortices, strong interaction between the wave and the structure. Models based on Smoothed Particle Hydrodynamics (SPH), that used a mesh-free technique, are an option to address wave overtopping and other phenomena involved on the interaction between waves and coastal structures. In the present paper, SPHysics model is validated and applied for wave propagation and wave overtopping of an impermeable seawall. Validation and convergence study is carried out considering several parameters such as the initial particle density and the eXSPH parameter. Free surface elevation in several gauges and overtopping discharge over the structure are analyzed and compared to experimental data and other numerical results. A very satisfactory agreement is obtained with experimental measurements. Finally, the numerical model is applied for modelling wave propagation with breaking and overtopping of an impermeable sea wall coastal defence structure, a common structure employed at the Portuguese coast. Numerical results are compared with experimental data from model scale tests carried at the National Civil Engineering Laboratory (LNEC). Good agreement is obtained for both free surface elevation and overtopping discharge over the structure.